2004
DOI: 10.1111/j.1464-410x.2005.05244.x
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluation of the Tumour‐Node‐Metastasis staging of locally advanced renal cortical tumours: absolute size (T2) is more significant than renal capsular invasion (T3a)

Abstract: OBJECTIVETo determine which factor was more predictive of adverse outcome in our institutional experience with T2N0M0 and T3N0M0 renal cortical tumours (RCTs) treated surgically, as the current TumourNode-Metastasis (TNM) staging system for RCTs differentiates between tumours of > 7.0 cm but confined to the renal capsule (T2) and tumours that extend through the renal capsule regardless of size (T3a). MATERIALS AND METHODSWe analysed our institutional database of surgical urological oncology for all patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 14 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…Therefore, this cultural effect may account for the relative low staging disease (5 patients, 50%, were T3a) in our HR group and also relative low T4 disease in our population. There were several reports suggesting that pT3a disease may have a better prognosis than pT2 disease, unless its size was greater than 7 cm [6,22,23]. Therefore, the higher proportion of T3a disease in our HR group may also partly explain the observed better survival rate of our patients, which was even better than our IR group.…”
Section: Discussionmentioning
confidence: 49%
“…Therefore, this cultural effect may account for the relative low staging disease (5 patients, 50%, were T3a) in our HR group and also relative low T4 disease in our population. There were several reports suggesting that pT3a disease may have a better prognosis than pT2 disease, unless its size was greater than 7 cm [6,22,23]. Therefore, the higher proportion of T3a disease in our HR group may also partly explain the observed better survival rate of our patients, which was even better than our IR group.…”
Section: Discussionmentioning
confidence: 49%
“…Murphy et al [12] compared T2 tumors to T3a tumors and found that the risk of metastasis was equivalent in both but that the T2 tumors actually demonstrated a worse disease-free survival.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, Murphy et al . reported worse outcomes for T2 disease compared with T3a disease, pushing the case for tumor size as a stronger prognostic factor . Lam et al .…”
Section: Discussionmentioning
confidence: 99%